The nature of the claim of lack of jurisdiction in the comparative and Iraqi administrative judiciary - Razaq, Azhar; Mohammed, Rasha (Journal of Legal Sciences, 2022)
The plea of ​​lack of jurisdiction is the most important formal defense in the administrative judiciary, it is a denial of the court’s authority in hearing the case for its deviation from the limits of the jurisdiction that the law has decided for it, and if that court issues a decision in pleading not to have jurisdiction directed at it, the matter does not deviate from one of two decisions, it is either to decide that it is She is competent to hear the case, so she refuses the payment and proceeds to examine the matter, or she decides to accept the defense of lack of jurisdiction raised by the litigants, or on her own if the matter is related to the public order, and she must here refer the case to the competent court, a procedure that is associated with the court’s decision that it does not have jurisdiction to hear the case, and where The theory of jurisdiction in the judiciary is generally based on elements represented by functional, specific and spatial jurisdiction.